Clinical Phenotype and Mutation Spectrum of the CYP21A2 Gene in Patients with Steroid 21-Hydroxylase Deficiency - Choi, J.-H.; Jin, H.-Y.; Lee, B. H.; Ko, J. M.; Lee, J.-J.; Kim, G.-H.; Jung, C.-W.; Lee, J.; Yoo, H.-W. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Steroid 21-hydroxylase deficiency is caused by inactivating mutations in the CYP21A2 gene. This paper reports on the mutation spectrum and the genotype-phenotype correlation of 21-hydroxylase deficiency. 72 unrelated patients with congenital adrenal hyperplasia (CAH) were included. Molecular analysis of CYP21A2 was performed, via the multiplex ligation-dependent probe amplification (MLPA) analysis and sequence-specific differenzial PCR amplification of the CYP21A2 and CYP21A1P genes, using 4 pair-wise sequence-specific primers, followed by sequencing of the entire CYP21A2 gene. Large gene deletions were identified in 45 (31.3%) of the 144 unrelated CAH alleles, whereas the most frequent point mutations were intron 2 splice mutations (c.293-13A>G) (41/144, 28.5%). The MLPA analysis successfully identified 23 of 72 patients (31.9%) with single copy deletion in CYP21A2. This paper describes a rapid and accurate method for the molecular diagnosis of 21-hydroxylase deficiency, which relies on the identification of point mutations and structural rearrangements within the CYP21A2 gene.
Keywords: Congenital adrenal hyperplasia; CYP21A2; Steroid 21-hydroxylase deficiency